Ekonomi Kreatif Berbasis Budaya Lokal - Fitria Fitria (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
This community service activity discusses talent development in the creative economy. Seen in terms of potential, in terms of opportunities and ways that can be taken to be able to develop a creative economy based on local culture. The purpose of this community service is to foster the curiosity of the students of SMK Muhammadiyah 4 Palembang in the creative economy. In today's digital era, where there are lots of opportunities for millennial children to channel their talents, such as being a YouTuber or entrepreneurship through online. With this community service, it is hoped that it will be able to provide an understanding to students that there are many things that can be done in this era, which can even increase their own income and more than that can help the economy of the family and the surrounding community.